Policy Implementation Challenges in Addressing Child Sexual Violence - Igobula, Sitna Aisa S.; Muchsin, Slamet; Musa, Ali Masykur (Academia Open, 2025)
General Background: The well-being and development of children are foundational to a nation's future. Specific Background: In Indonesia, despite existing child protection laws, sexual violence against children remains a persistent issue, including in Malang City. Knowledge Gap: There is limited analysis of how local protective policies are implemented and what challenges hinder their effectiveness. Aims: This study aims to identify and evaluate the policy implementation of child sexual assault response in Malang, focusing on procedures, enabling factors, and obstacles. Results: The findings reveal that the UPT PPA operates under a supportive legal framework but faces barriers such as limited human resources, low public awareness, weak community engagement, and issues in case reporting consistency. Novelty: This study contributes a contextualized understanding of the operational challenges within a local child protection agency in Indonesia. Implications: The results highlight the need for targeted capacity building, improved reporting mechanisms, and broader community involvement to enhance the effectiveness of protective policies for children in Malang. Highlights: Highlights the gap between legal protection and practical implementation. Identifies key barriers such as low awareness and limited resources. Emphasizes the role of local agencies like UPT PPA in safeguarding children. Keywords: Policy Implementation, Sexual Violence, Child Protection